Nitrate residual as a key parameter to efficiently control partial denitrification coupling with anammox. (4th June 2019) - Le, Tri; Peng, Bo; Su, Chunyang; Massoudieh, Arash; Torrents, Alba; Al‐Omari, Ahmed; Murthy, Sudhir; Wett, Bernhard; Chandran, Kartik; deBarbadillo, Christine; Bott, Charles; De Clippeleir, Haydée
Abstract : Abstract: Despite the increased research efforts, full‐scale implementation of shortcut nitrogen removal strategies has been challenged by the lack of consistent nitrite‐oxidizing bacteria out‐selection. This paper proposes an alternative path using partial denitrification (PdN) selection coupled with anaerobic ammonium‐oxidizing bacteria (AnAOB). A nitrate residual concentration (>2 mg N/L) was identified as the crucial factor for metabolic PdN selection using acetate as a carbon source, unlike the COD/N ratio which was often suggested. Therefore, a novel and simple acetate dosing control strategy based on maintaining a nitrate concentration was tested in the absence and presence of AnAOB, achieving PdN efficiencies above 80%. The metabolic‐based PdN selection allowed for flexibility to move between PdN and full denitrification when required to meet effluent nitrate levels. Due to the independence of this strategy on species selection and management of nitrite competition, this novel approach will guarantee nitrite availability for AnAOB under mainstream conditions unlike shortcut nitrogen removal approaches based on NOB out‐selection. Overall, a COD addition of only 2.2 g COD/g TIN removed was needed for the PdN‐AnAOB concept showing its potential for significant savings in external carbon source needs to meet low TIN effluent concentrations making this concept a competitive alternative. Practitioner points: Nitrate residual is the key control parameter for partial denitrification selection. Metabolic selection allowed for flexibility of moving from partial to full denitrification. 2.2 g COD/g TIN removed was needed for partial denitrification‐anammox process. Abstract : PdN‐AnAOB route for mainstream shortcut N removal without NOB out‐selection.